Work motivation and associated factors among nurses working in public hospitals of the Wolaita Zone, Southern Ethiopia - Senbetu, Bereket Dejene; Debancho, Wadu Wolancho; Jemaneh, Tsiyon Mekoya; Jima, Serkalem Aschalew; Hardido, Temesgen Geta; Gerete, Tamirat Beyene (Frontiers in Health Services, 2025)
BackgroundNurses’ work motivation encompasses their readiness to perform effectively and achieve designated tasks and objectives. Providing high-quality nursing care becomes significantly more challenging in the absence of motivated nurses and a supportive healthcare environment. Nevertheless, there is a paucity of empirical research examining the work motivation of nurses. Hence, this study aimed to assess the level of work motivation and its associated factors among nurses working in public hospitals in the Wolaita Zone.MethodsAn institutional-based cross-sectional study involving 419 nurses and 12 key informants was conducted using a mixed-methods method. Quantitative data were collected using a simple random sampling technique, while qualitative data were collected using purposive sampling. Data were collected using pretested self-administered questionnaires and in-depth interviews. Statistical Package for Social Science version 26 was used for statistical analysis. Bivariate and multivariable logistic regression analyses were performed to identify factors associated with work motivation. Statistical significance was determined using AORs with 95% CIs and p-values of less than 0.05.ResultsA total of 394 participants were included, yielding a response rate of 94%. About 202 nurses (51.3%; 95%CI: 46.4–56.9) reported being motivated. Several factors were negatively associated with nurses’ work motivation: type of institution (AOR = 0.406; 95% CI: 0.236–0.699; p = 0.001), workload (AOR = 0.495; 95% CI: 00.297–0.827; p = 0.007), negative perceptions of respect and benefits for nurses in organizations (AOR = 0.351; 95% CI: 0.180–0.682; p = 0.002), negative perceptions of leadership in hospitals [(AOR = 0.487; 95% CI: 0.240,0.985; p = 0.045). In contrast, nurses with 1–5 years of work experience were likely to be motivated (AOR = 3.29; 95% CI: 1.101–9.846; p = 0.003). The analysis revealed themes related to structural-administrative factors, socio-economic factors, and individual nurse-related factors.ConclusionThe results reveal that approximately 50% of the nursing participants expressed low levels of work motivation. Significant factors influencing nurses’ motivation included the type of institution, years of work experience, workload, perceptions of respect and benefits, and quality of leadership in hospitals.